(untitled) (Journal of Plant Disease Sciences, 2025)
Biosynthesized -based copper nanoparticles (CuNPs), obtained from the Department of Plant Pathology, PDKV Akola, were evaluated for their effects on soybean ( L. Merrill) seed performance. Seed treatments were applied at concentrations of 10 ppm, 50 ppm, 100 ppm, 150 ppm, 200 ppm, and 250 ppm, and assessed for their impact on seed germination, root length, shoot length, seedling vigour index, and pre- and post-emergence mortality. The results indicated that seed treatment with -based CuNPs at 10 ppm was the most effective concentration, significantly reducing the adverse effects of seed- borne mycoflora and promoting optimal seedling growth. Specifically, this concentration enhanced seed germination and seedling vigour while minimizing both pre- and post-emergence mortality. In contrast, higher concentrations (@ 50 ppm) of -based CuNPs exhibited phytotoxic effects, leading to a reduction in germination rate, root and shoot growth, seedling vigour, and an increase in mortality. These findings suggest that lower concentrations of biosynthesized CuNPs are beneficial for seed treatment, whereas elevated doses may exert detrimental effects on soybean seedling development.